Government Insurance and Out-of-Pocket Healthcare Expenditure in Ghana. Issue 3 (4th March 2023) - Ampaw, Samuel; Appleton, Simon; Lou, Xuyan
Abstract: The relationship between membership in Ghana's national health insurance scheme and out-of-pocket healthcare expenditure (OOPHE) was quantified using data from two rounds of the Ghana Living Standards Survey for 2013 and 2017. Censored quantile regressions were evaluated with and without instrumental variables. The results show that going from having no insured household member to all insured predicted less OOPHE (by 19% at the median). We find statistically significant differences between the 2013 and 2017 estimates. Insurance reduced OOPHE in 2013 but had a statistically insignificant effect in 2017. The effect on spending on outpatient care was greater than that related to medicine and medical supplies. There was no statistically significant relationship with hospitalisation fees. Falling government health spending and growing reliance on private healthcare financing have been observed. The insurance scheme has become less generous, and it was therefore less effective in 2017.